PENGEMBANGAN PROGRAM PENANGANAN GANGGUAN PEMUSATAN PERHATIAN HIPERAKTIF ( GPPH ) SISWA DI SEKOLAH DASAR - WIDAJATI, WIWIK (Pendidikan Dasar, 2009)
Abstract: This research in develop behaviour therapy program, behaviour modification, play with music that teacher to get attention grasp from students (GPPH) especially elementary level (SD, MI, SLB). Long research purpose is increase ability to handle students problem that get learning difficulty and low prestige, one lost grasp attention deficit hyperactive disorder (GPPH). GPPH is done to overcome students result optimally.Certain purpose of this research is develop teacher ability to handle students to get grasp attention deficit hyperactive disorder students by using behaviour therapy program, behaviour modification, play and music therapy involves arranging behaviour therapy program, behaviour modification, play and music therapy to make teacher optimally.